“Artificial Intelligence”: Philosophical Aspects of Understanding - Naumenko, Oleg; Utkir, Sapaev; Skatershchikova, Alla; Bekbaev, Rauf (Տիգրան Մեծ)
The problem of “artificial intelligence” is becoming more and more relevant today. This topic is also of great interest to philosophers. This article considers primarily a retrospective analysis of the study of the possibilities of artificially created mechanisms that first perform primitive actions and then more complex ones, including thought processes. Then the article provides a particularphilosophical analysis of the con-cept of “artificial intelligence”, its capabilities and potential danger.
Keywords: Philosophy